The absence of AQP4/TRPV4 complex substantially reduces acute cytotoxic edema following ischemic injury - Sucha, Petra; Hermanova, Zuzana; Chmelova, Martina; Kirdajova, Denisa; Camacho Garcia, Sara; Marchetti, Valeria; Vorisek, Ivan; Tureckova, Jana; Shany, Eyar; Jirak, Daniel; Anderova, Miroslava; Vargova, Lydia (Frontiers in Cellular Neuroscience, 2022)
Astrocytic Aquaporin 4 (AQP4) and Transient receptor potential vanilloid 4 (TRPV4) channels form a functional complex that likely influences cell volume regulation, the development of brain edema, and the severity of the ischemic injury. However, it remains to be fully elucidated whether blocking these channels can serve as a therapeutic approach to alleviate the consequences of having a stroke. In this study, we used in vivo magnetic resonance imaging (MRI) to quantify the extent of brain lesions one day (D1) and seven days (D7) after permanent middle cerebral artery occlusion (pMCAO) in AQP4 or TRPV4 knockouts and mice with simultaneous deletion of both channels. Our results showed that deletion of AQP4 or TRPV4 channels alone leads to a significant worsening of ischemic brain injury at both time points, whereas their simultaneous deletion results in a smaller brain lesion at D1 but equal tissue damage at D7 when compared with controls. Immunohistochemical analysis 7 days after pMCAO confirmed the MRI data, as the brain lesion was significantly greater in AQP4 or TRPV4 knockouts than in controls and double knockouts. For a closer inspection of the TRPV4 and AQP4 channel complex in the development of brain edema, we applied a real-time iontophoretic method in situ to determine ECS diffusion parameters, namely volume fraction (α) and tortuosity (λ). Changes in these parameters reflect alterations in cell volume, and tissue structure during exposure of acute brain slices to models of ischemic conditions in situ, such as oxygen-glucose deprivation (OGD), hypoosmotic stress, or hyperkalemia. The decrease in α was comparable in double knockouts and controls when exposed to hypoosmotic stress or hyperkalemia. However, during OGD, there was no decrease in α in the double knockouts as observed in the controls, which suggests less swelling of the cellular components of the brain. Although simultaneous deletion of AQP4 and TRPV4 did not improve the overall outcome of ischemic brain injury, our data indicate that the interplay between AQP4 and TRPV4 channels plays a critical role during neuronal and non-neuronal swelling in the acute phase of ischemic injury.